Barriers to implementing simulation-based surgical training for improving quality and safety in developing countries: A short communication - Abdullah Saeed Khan; Selina Hasan; Faisal Wasim Ismail; Nadeem Siddiqui (Journal of the Pakistan Medical Association, 2026)
Simulation-based surgical training has the potential to significantly improve surgical outcomes in developing countries. However, its implementation faces numerous challenges, including financial constraints, infrastructural limitations, cultural barriers, and a lack of trained personnel. High costs, limited access to technology, and resistance to innovative teaching methods hinder the adoption of simulation-based surgical training. To overcome these obstacles, strategic approaches are needed, such as leveraging low-fidelity simulators, building strong partnerships, and investing in faculty development. By addressing these challenges, developing countries can harness the power of simulation-based surgical training to enhance surgical education and improve patient care. Keywords: Simulation training, Surgical procedures, Developing countries, Healthcare quality, Patient safety.